Everything happens somewhere: using webGIS as a tool for sustainable natural resource management. Issue 10 (1st December 2003) - Kearns, Faith R.; Kelly, Maggi; Tuxen, Karin A.
Abstract : Whether tracking invasive species, assessing water quality, or monitoring the spread of disease, comprehensive data collection is a key component of sustainable natural resource management. Increasingly, fostering community‐based monitoring is seen as a valuable way to augment data gathering and enhance public involvement in environmental management. However, growing quantities of data and increasing interest from the public and decision makers create technical data storage and access issues. Although not yet widely used in natural resource management, Web‐based Geographic Information Systems (webGIS), a hybrid of GIS and Internet technologies, are a promising option for entering and storing heterogeneous datasets, indexed by location, and making them widely available in a visual, dynamic, and interactive format. Although webGIS has the potential to increase public participation in environmental management, there are technical, institutional, and social challenges to its implementation and usage that need to be addressed, including differential Internet access, training, and privacy.